CORPORATE GOVERNANCE DAN PENGUNGKAPAN ENTERPRISE RISK MANAGEMENT (ERM): STUDI EMPIRIS PERUSAHAAN NON KEUANGAN INDONESIA - Hudi Kurniawanto; Bambang Widarno (Universitas Slamet Riyadi, 2020)
The purpose of this study is to examine the effect of corporate governance on enterprise risk management disclosure in Indonesia. Corporate governance is defined as size of the board of commissioners and the proportion of independent commissioners. This study also uses firm size as a control variable.The samples are selected using purposive sampling, with 117 annual reports from non-financial companies listed in Indonesia Stock Exchange in the year 2014-2016. The results of this study prove that size of the board of commissioners has effects on enterprise risk management disclosure, while the proportion of independent commissioners does not affect enterprise risk management disclosure. Variable company size in this study affect enterprise risk management disclosure. This shows that the greater the number of commissioners, the better the level of supervision and pressure on management, thus encouraging management to be more transparent in disclosing enterprise risk management.Keywords: Enterprise risk management disclosure, Corporate Governance, Non-financial company listed on the Indonesia Stock Exchange